Synthesize and characterization of new polymeric surfactants based on nonionic maleate surfmer by catalytic bulk copolymerization with methyl methacrylate - Sanaa M. Solyman; E.A. Elsharaky; Amira E. El-Tabey (Egyptian Journal of Petroleum)
Non-ionic maleate surfmer (M1) was prepared via ring opening reaction of maleic anhydride with hexanol followed by esterfaction with polyethylene glycol. The prepared surfmer was homo-polymerized and copolymerized with methyl methacrylate (M2) at different conditions using TiO2 and V2O5 as catalysts in presence of O2 or N2. The chemical structure of the prepared surfmer, homo-polymer and copolymer were confirmed by FT-IR, 13C and 1H NMR. The molecular weights of the prepared polymers were measured using Gel Permeation Chromatography (GPC) and their thermal gravimetric analysis (TGA) was determined. TGA indicated a higher thermal stability for the copolymers M1M2TN and M1M2VO relative to the pure polymethylmethacrylate (PMMA). The interfacial tension for the prepared surfmer and the copolymer was measured. The optimum conditions which resulted in 64.2% and 63.8% conversion were 20% w/w TiO2 in N2 and 10% w/w V2O5 in O2 at 80 °C for 4 h with M1/M2 molar ratio of 1:1. Keywords: Catalytic copolymerization, Maleate surfmer, Methyl methacrylate, Interfacial tension, Polymeric surfactants